Foot pain: uncommon presentation of lung cancer. (16th July 2012) - Lamarca, Angela; Hindi, Nadia; Belda-Iniesta, Cristobal; de Castro, Javier
Abstract : Acrometastases is an unusual presentation of bone metastases, specially when they are the unique location of bone metastases. The authors report a case of a men diagnosed with a lung adenocarcinoma with a unique lytic acrometastases in his left foot. He has been treated with systemic chemotherapy with good local and systemic response. The most common sites of bone metastases are the vertebrae, pelvis, ribs, sternum and skull. Bone metastases in the distal regions of the extremities are unusual (from 0.007 to 0.3% of all patients with bone metastases), involving more frequently hands than feet.